Partial Interpretations and Company: Beckett, Foucault, et al. and the Author Question - Jim Hicks (Studies in 20th & 21st Century Literature, 1993)
This essay examines recent debate on the status of the author in contemporary literature by means of an extended analysis of Samuel Beckett's Company. A number of critical responses to the Beckett text— Wayne Booth's reading in The Rhetoric of Fiction is taken as symptomatic—are criticized for their recuperation of the author-function in a text which moves beyond such well-wom routes of inquiry. Company is read as an inevitably incomplete attempt to read "anachronistically," i.e. to expand (and contract) story, discourse, and discursive positions starting from the necessary fiction of a present-tense (from, to cite Gilles Deleuze, "il y a du langage"). It is concluded that, in any case, constructions of "Beckett" by literary critics do not rid us of the implications of Beckettian discourse; instead, it is the Beckettian discourse that will rid us of "Beckett."
Keywords: author; contemporary literature; Samuel Beckett; Company; Wayne Booth; The Rhetoric of Fiction; symptomatic; author-function; anachronistically; discourse; present-tense; Gilles Deleuze; Beckett; Beckettian; Focault